Prognostic predictors of adrenocortical carcinoma: A single-center thirty-year experience - Pan, Li-Hsin; Yen, Chueh-Chuan; Huang, Chun-Jui; Ng, Xin-Ning; Lin, Liang-Yu (Frontiers in Endocrinology, 2023)
Background: The prognosis of adrenocortical carcinoma (ACC) is poor but highly variable. The present study aimed to characterize patients with ACC at a single center in Taiwan and to determine the prognostic predictors of overall and progression-free survival. Methods: Medical records of patients, who were diagnosed with ACC at Taipei Veterans General Hospital between January 1992 and June 2021, were reviewed. Patient demographics, tumor characteristics, and subsequent treatment were analyzed with regard to overall survival and progression-free survival using Kaplan-Meier methods and a Cox regression model. Results: Sixty-seven patients were included. Females (65.7%) were more susceptible to ACC, with a younger onset and active hormonal secretion. One-half of the patients exhibited distant metastases at the time of diagnosis. The European Network for the Study of Adrenal Tumours (ENSAT) stage (hazard ratio [HR] 3.60 [95% confidence interval (CI) 1.25–10.38]; p=0.018), large vessel invasion (HR 5.19 [95% CI 1.75–15.37]; p=0.003), and mitotane use (HR 0.27 [95% CI 0.11–0.70]; p=0.007) were significantly associated with overall survival (OS). There was no single factor independently associated with progression-free survival. Conclusion: ENSAT stage had a substantial impact on overall survival though there was no difference in OS between patients with stage II and stage III ACC. Large vessel invasion portended poor prognosis and influenced OS significantly. Moreover, mitotane only improved clinical outcomes of patients with stage IV disease.